Babbitt - Keighley, William, 1889-1984; McCall, Mary C., 1904-1986; Reed, Tom, 1901-1961; Busch, Niven, 1903-1991; Markson, Ben; MacMahon, Aline, 1899-1991; Kibbee, Guy, 1882-1956; Dodd, Claire, 1908-1973; Lewis, Sinclair, 1885-1951.; First National Pictures, Inc.; United Artists Collection (Library of Congress) (United States : First National Pictures, Inc., 1934)
Realtor George F. Babbitt lives with his wife Myra and his two children, Verona and Ted, in the fast growing town of Zenith. Popular and successful, he is elected Grand Ringmaster of his lodge, the Zebras. Babbitts's troubled friend shoots his wife and only he stands by him. Myra leaves him and he spends too much time with a widower, Tanis Judique. Babbitt is part of a questionable land deal, the details of which Tanis tries to ply out of him so she can blackmail the other involved parties. When she is unsuccessful and he cannot pay her off, she tells her story to the newspapers. He is disgraced and is forced to resign from the Zebras. He confesses his problems to Myra, who figures out a way to make him look like a hero instead of a villain. The Zebras ask him to return to the lodge.
Copyright: Warner Bros. Pictures, Inc.; 15Dec34; LP5175.
On credits: Warner Bros. Pictures, Inc. & The Vitaphone Corp. presents; sources cited below give First National Pictures as distributor except AFI catalog : feature films, 1930-1939, p. 97 which lists First National and Vitaphone Corp. as distributors; AFI catalog indicates First National was controlled by Warner Bros. Pictures.
Summary taken from AFI catalog : feature films, 1930-1939, p. 97.
Production Code Administration certificate no. 349.
Production no. 869.
NCN009602; Babbitt.
Keywords: Middle-aged men -- United States -- Drama; Businessmen -- United States -- Drama; Conformity -- Drama; Marriage -- United States -- Drama; Fraternal organizations -- United States -- Drama; Social status -- United States -- Drama; Sociological films and programs; Melodrama; Adaptations; Features